2012
DOI: 10.1159/000338925
|View full text |Cite
|
Sign up to set email alerts
|

Is Preterm Delivery Indicated in Fetuses with Gastroschisis and Antenatally Detected Bowel Dilation?

Abstract: Introduction: Due to the controversy surrounding diagnostic ultrasound evaluations and elective preterm delivery of fetuses with gastroschisis, we sought to calculate the predictive value of bowel dilation in fetuses with gastroschisis and evaluate the effect of preterm delivery on neonatal outcomes. Materials and Methods: Ultrasounds and medical records of 103 mother-infant pairs with fetal gastroschisis were reviewed. Eighty-nine pairs met the criteria. Intestinal complications, gestational age at delivery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
17
0
2
Order By: Relevance
“…The types of testing performed were also consistent with the recommendations in the literature, although the significance of each test remains controversial. The NST (55%; 72/129) and BPP (50%; 63/126) were two of the more consistently utilized surveillance tests in our study, similar to a number of studies reported in the literature [7, 24-26]. While ultrasound for EFW was performed weekly by the majority of providers (79%; 104/131), at least two other studies disagreed on its ability to accurately predict adverse outcomes [27, 28].…”
Section: Discussionsupporting
confidence: 80%
“…The types of testing performed were also consistent with the recommendations in the literature, although the significance of each test remains controversial. The NST (55%; 72/129) and BPP (50%; 63/126) were two of the more consistently utilized surveillance tests in our study, similar to a number of studies reported in the literature [7, 24-26]. While ultrasound for EFW was performed weekly by the majority of providers (79%; 104/131), at least two other studies disagreed on its ability to accurately predict adverse outcomes [27, 28].…”
Section: Discussionsupporting
confidence: 80%
“…The predictive value for adverse perinatal outcome of different thresholds of bowel dilatation at the last prenatal ultrasound has been previously studied [16,26,27,28,29,30,31,32,33,34,35]. Controversially, Page et al [36] in a recent systematic review concluded that IABD seen on an antenatal ultrasound scan is not a finding associated with an increased risk of adverse perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated, as other groups [29,32], that IABD is a strong ultrasound predictor of complex GS. Adjusting for gestational age improved the predictive accuracy of this indicator compared to fixed threshold models [34,35]. Interestingly, in 2 cases, IABD seen during the second trimester regressed spontaneously, advocating for caution when interpreting this ultrasound finding early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroschisis patients are often delivered preterm, either electively owing to preterm labor or owing to complications of pregnancy. Various outcomes have been reported in the literature related to this topic, and the results have been mixed [1,2,7,10,[12][13][14][15]. There are some reports of worse outcomes with early delivery, including an increased risk of infectious complications and poorer long-term neurodevelopmental outcomes [8,12].…”
Section: Discussionmentioning
confidence: 99%